2000
DOI: 10.1017/s0022029900004453
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic programming to investigate financial impacts of mastitis control decisions in milk production systems

Abstract: S. An adaptive stochastic dynamic programming model was used to solve the optimum replacement decision problem for the dairy cow under a range of alternative mastitis control procedures. The model predicted that reducing milk yield losses and somatic cell count penalties by using milking machine test, postmilking teat disinfection and dry cow therapy added approximately £4, £10 and £13 respectively to an original annuity equivalent net present value for the replacement heifer of £286. Assuming that these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 0 publications
1
26
0
1
Order By: Relevance
“…Despite the high economic damage of mastitis (Table 1), the most recent paper found on calculating the average cost of mastitis is almost 10 years old. (52,53). In some publications (1,20,25,29,45), results were presented in such a way that we could not transform them to data that could be compared to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high economic damage of mastitis (Table 1), the most recent paper found on calculating the average cost of mastitis is almost 10 years old. (52,53). In some publications (1,20,25,29,45), results were presented in such a way that we could not transform them to data that could be compared to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of mastitis on future milk yield of a cow, milk quality (fat and protein content, SCC), reproductive traits and length of productive life have to be added to the direct CM losses, for example, when comparing costs for mastitis control programs with the financial benefits of decreasing CM incidence (Yalcin and Stott, 2000;Seegers et al, 2003). The objective of the present study was to estimate the economic value of mastitis incidence in line with the breeding goal or the aggregate genotype.…”
Section: Comparison Estimates Of Economic Values For Scs By Three Metmentioning
confidence: 99%
“…Economic analysis comparing the use of dry cow antibiotic or internal teat sealant is not available. Most economic analyses have concluded that the use of dry cow antibiotic can be financially beneficial either in terms of effect on increased milk yield, lower SCC or reduced clinical mastitis compared with untreated cows (Berry et al 1997;Allore et al 1998 ;Yalcin et al 1999;Yalcin & Stott, 2000;Oliver et al 2003). Deciding which strategy to use, at the individual cow level, can be helped by decision tree analysis.…”
mentioning
confidence: 99%